The Influence of Powerpoint-Based Discovery Learning Models on Biology Student Learning Outcomes - Sariam Sariam; Hasmi Syahputra Harahap (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This study aims to determine the effect of the Power Point-Based Discovery Learning learning model on the learning outcomes of biology students on the circulatory system material in humans at MAS PP Nurul Huda Bangai. The research method used is quantitative research in the form of Quasi Experimental Design using a pretest-posttest control design. The PowerPoint-based Discovery Learning learning model is taught in class XI-A and the conventional learning model is taught in class XI-B. The instrument used in this study was a multiple-choice test for student learning outcomes. The data analysis technique used in this study is the Mann-Whitney technique using the SPSS 23.0 for Windows program. The results showed that there was an effect of the Power Point-Based Discovery Learning learning model on the learning outcomes of biology students (P=0.000<0.05), with the average score and standard deviation of the posttest in the Discovery Learning class 77.97 ± 10,848 and the average value and the posttest standard deviation in the conventional class was 69.82 ± 5.348. The results of this study are expected that teachers can apply the Power Point-Based Discovery Learning learning model when teaching the circulation system material in humans to improve student learning outcomes.